2018
DOI: 10.1007/s13304-018-0511-y
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and emergency surgery in the elderly: protocol of a prospective, multicenter study in Italy for evaluating perioperative outcome (The FRAILESEL Study)

Abstract: Improvements in living conditions and progress in medical management have resulted in better quality of life and longer life expectancy. Therefore, the number of older people undergoing surgery is increasing. Frailty is often described as a syndrome in aged patients where there is augmented vulnerability due to progressive loss of functional reserves. Studies suggest that frailty predisposes elderly to worsening outcome after surgery. Since emergency surgery is associated with higher mortality rates, it is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…[17] When a surgical intervention was scheduled for an elderly patient, long-term hospitalization, dependency, home care requirement, institutionalization and even death are the possible outcomes. [18] A previous report indicated that patients with functional dependency have higher 30-day mortality rates than independent patients after major general and vascular surgery. [19] The dependency of the patients was also found to be a significant factor on the ICU admission in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[17] When a surgical intervention was scheduled for an elderly patient, long-term hospitalization, dependency, home care requirement, institutionalization and even death are the possible outcomes. [18] A previous report indicated that patients with functional dependency have higher 30-day mortality rates than independent patients after major general and vascular surgery. [19] The dependency of the patients was also found to be a significant factor on the ICU admission in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decisions, including operative technique, were based on the criteria of individual centers and attending surgeons. The investigators were informed about the objectives of the study and asked for complete details about the surgical management of acute abdomen in elderly patients following standard methods and collection protocols [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FRAILESEL study investigates over 130 variables [ 8 ], exploring 5 domains such as patient demographic and clinical data, preoperative risk factors and operative variables, frailty condition, and postoperative outcome and follow-up. Data collected included patient demographic characteristics (age, gender, weight, height, social status), medical and surgical history (comorbidities), common preoperative biochemical blood examination (including PCR, PCT and arterial blood gas analysis), pathological features, and operative details.…”
Section: Methodsmentioning
confidence: 99%
“…In Italy, according to the Italian National Institute for Statistics (Istituto Nazionale di Statistica, ISTAT), there were approximately 13.5 million people aged 65 and older in 2016, representing 22.3% of inhabitants [3,4], and this value will continue to grow in the following years. Recovery, particularly for surgical emergencies, is considered complicated in the elderly [5][6][7], who tend to have longer hospital stays [7][8][9] (this is related to comorbidities, an elevated number of drugs taken, and reduced physical and mental reserves) [3,5,8,9]. Not all patients of the same age have the same risks or frailty issues (in Surgeries 2021, 2 120 multiple physiological systems, this is defined as age-related cumulative decline, and is considered a better predictor of mortality and morbidity than chronological age in the elderly).…”
Section: Aimmentioning
confidence: 99%
“…Despite the urgent need for knowledge in treating elderly and/or frail surgical patients, especially in emergency situations, there are surprisingly few population-based studies [9,[11][12][13][14][15][16] that involve long-term follow-ups. For this reason, our Santa Maria Regina della Misericordia Hospital, General Surgery Department, in Adria (Italy) participated in a study dubbed frailty and emergency surgery in the elderly: protocol of a prospective, multicenter study in Italy for evaluating perioperative outcome (FRAILE-SEL) [3]. Our evaluation started with a standardized evaluation of urgent admissions for surgical interventions in elderly, consequently we considered the Fried frailty score criteria at recovery.…”
Section: Aimmentioning
confidence: 99%